Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/nyas.13276
|View full text |Cite
|
Sign up to set email alerts
|

Utility of preclinical drug versus food choice procedures to evaluate candidate medications for methamphetamine use disorder

Abstract: Substance use disorders are diagnosed as a manifestation of inappropriate behavioral allocation towards abused drugs and away from other behaviors maintained by more adaptive nondrug reinforcers (e.g., work and social relationships). Substance use disorder treatment goals include not only decreasing drug-maintained behavior but also promoting behavioral reallocation toward these socially adaptive alternative reinforcers. Preclinical drug self-administration procedures that offer concurrent access to both drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 115 publications
1
10
0
Order By: Relevance
“…Examples of recent pharmacological variables that have either decreased or increased drug versus food choice are listed in Table 1. Preclinical drug versus food choice procedures evaluating subchronic pharmacological treatments have produced concordant results with both human laboratory drug self-administration studies and double-blind, placebo-controlled clinical trials for cocaine [16], opioids [53], and methamphetamine [54]. Three examples where this translational concordance between preclinical drug versus food-choice procedures, human laboratory drug versus money choice procedures, and double-blind, placebo-controlled clinical trials has been recently revealed are described below.…”
Section: Pharmacological Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of recent pharmacological variables that have either decreased or increased drug versus food choice are listed in Table 1. Preclinical drug versus food choice procedures evaluating subchronic pharmacological treatments have produced concordant results with both human laboratory drug self-administration studies and double-blind, placebo-controlled clinical trials for cocaine [16], opioids [53], and methamphetamine [54]. Three examples where this translational concordance between preclinical drug versus food-choice procedures, human laboratory drug versus money choice procedures, and double-blind, placebo-controlled clinical trials has been recently revealed are described below.…”
Section: Pharmacological Determinantsmentioning
confidence: 99%
“…Furthermore, a recent analysis of d -amphetamine treatment effects on cocaine versus food choice suggested that d -amphetamine increased the relative price of cocaine compared with the alternative nondrug reinforcer [66]. However, the effectiveness of an ‘agonist-like’ pharmacotherapy approach does not completely translate to other substance-use disorders, such as methamphetamine [54]; and the effectiveness of ‘agonist-like’ pharmacotherapy approaches on preclinical nicotine versus nondrug choice is unknown. Overall, this body of literature suggests that candidate pharmacotherapies that share pharmacological attributes with some, but not all, abused drugs hold the most promise in both decreasing behaviors maintained by drugs and increasing behaviors maintained by alternative reinforcers.…”
Section: Pharmacological Determinantsmentioning
confidence: 99%
“…Although preclinical studies have previously shown opioid-targeted vaccines to reduce rates of opioid self-administration [12][13][14][15], there are no published studies examining whether opioid-targeted vaccines would not only decrease opioid-taking behaviors, but also increase behavior directed towards more adaptive nondrug reinforcers, consistent with OUD treatment goals [16,17]. Thus, a fentanyl-vs.-food choice procedure was used because preclinical choice procedures have increasingly shown translational concordance to both human laboratory studies and double-blind placebo-controlled clinical trials in the evaluation of candidate medications for substance use disorders [18][19][20]. Two experimental conditions were examined.…”
Section: Introductionmentioning
confidence: 99%
“…In these models, it may be argued that drugseeking is driven by lack of an alternative, rather than increased motivation to obtain the drug [6]. A number of different preclinical models have been developed that incorporate choice of alternative reinforcers, such as concurrent access [7,8], and the focus of the present work, the discrete choice procedure [9].…”
Section: Introductionmentioning
confidence: 99%